Pemanfaatan Limbah Geo Dipa Dalam Pembuatan Septic Tank : Menuju Lingkungan Bersih (Towards a Clean Environment) - Amelia Agustina; Muhammad Albaz Ulumudin; Nur Kholifah; Ahmad Alfin; Wiji Lestarini (CATHA SAINTIFICA, 2025)
Environmental issues, particularly waste management, remain a serious challenge in Indonesia. One of the industries contributing to solid waste is geothermal power generation, which produces silica residues that have not been fully utilized. This study explores the potential use of Geodipa silica waste as a partial substitute in septic tank culvert concrete mixtures to improve structural performance and support sustainable waste management. The experimental method was carried out at the Civil Engineering Laboratory of Universitas Sains Al-Qur’an by preparing cylindrical specimens with 5%, 8%, and 12% waste variations. Compressive strength tests were performed after seven days of curing. The results showed that the highest compressive strength was achieved at an 8% waste addition, reaching 97.4 MPa, which significantly exceeds the strength of normal concrete at 38.5 MPa. Meanwhile, the 5% and 12% variations showed lower performance compared to the 8% mixture. Cost analysis also indicated that the use of Geodipa waste reduced material expenses compared to normal culverts. These findings highlight that incorporating Geodipa waste into concrete not only enhances strength and cost efficiency but also contributes to environmental sustainability through industrial waste utilization. This innovation has strong potential for application in sanitation infrastructure, particularly septic tank culverts.